Le voyage virtuel. Les consommatrices, le monde de l'étranger et Eaton à Montréal, 1880-1980 - O'Donnell, Lorraine (Revue d'histoire de l'Amérique française, 2005)
issued: 2005-21-00
Keywords: Eaton; Femmes; Magasins

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins